Farmers' Decision Making on Livestock Trading Practices: Cowshed Culture and Behavioral Triggers Amongst New Zealand Dairy Farmers - Hidano, Arata; Gates, M. Carolyn; Enticott, Gareth (Frontiers in Veterinary Science, 2019)
Studies of farmers’ failure to implement biosecurity practices frequently frame their behaviour as a lack of intention. More recent studies have argued that farmers’ behaviours should be conceptualised as emergent from farming experiences rather than a direct consequence of specific intentions. Drawing on the concepts of ‘cowshed’ culture and the ‘Trigger Change Model’, we explore how farmers’ livestock purchasing behaviour is shaped by farms’ natural and physical environments and identify what triggers behavioural change amongst farmers. Using bovine tuberculosis (bTB) in New Zealand as a case example, qualitative research was conducted with 15 New Zealand dairy producers with varying bTB experiences. We show how farmer’s livestock purchasing behavior evolve with culture under a given farm environment. However, established cultures may be disrupted by various triggers such as disease outbreaks, introductions of animals with undesired characteristics, and farm relocation. While dealing with economic and socio-emotional impacts posed by triggers, farmers reorganise their culture and trading behaviours, which may involve holistic biosecurity strategies. Nevertheless, we also show that these triggers instigate only small behavioural changes for some farmers, suggesting the role of the trigger is likely to be context-dependent. Using voluntary disease control schemes such as providing disease status of source farms has attracted great interest as a driver of behavioural change. One hopes such schemes are easily integrated into existing farm practices, however, we speculate such an integration is challenging for many farmers due to path-dependency. We therefore argue that these schemes may fail to bring their intended behavioural changes without a greater understanding of how different types of triggers work in different situations. We need a paradigm shift in how we frame farmer’s livestock trading practices. Otherwise, we may not able to answer our questions about farm biosecurity if we continue to approaching these questions solely from a biosecurity point of view.